1988
DOI: 10.1126/science.3175623
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Protects Against Light Damage in the Rat Retina

Abstract: An increase in the synthesis of heat shock proteins that is induced in cells in vitro by hyperthermia or other types of metabolic stress correlates with enhanced cell survival upon further stress. To determine if a similar increase in stress tolerance could be elicited in vivo, rats were made hyperthermic, and then their retinas were tested for sensitivity to light damage. This treatment resulted in a marked decrease in photoreceptor degeneration after exposure to bright light as compared to normothermic anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
1
4

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(175 citation statements)
references
References 20 publications
4
166
1
4
Order By: Relevance
“…The phenomenon of induced tolerance was also observed in in vivo mammalian cells. Barbe et al (1988) made rats hy perthermic and showed that the retina was less sen sitive to light damage compared to untreated con trols. This change was correlated to protein synthe sis in the retina after hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of induced tolerance was also observed in in vivo mammalian cells. Barbe et al (1988) made rats hy perthermic and showed that the retina was less sen sitive to light damage compared to untreated con trols. This change was correlated to protein synthe sis in the retina after hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, short-term total body heat-stress has been shown to prevent light-induced damage to the photoreceptors in the retina, ischemia-induced death of hippocampal neurons and cardiac myocytes, carbon tetrachlorideinduced hepatotoxicity, and lipopolysaccharideinduced pulmonary fibrosis (Barbe et al 1988;Chopp et al 1989;Marber et al 1993;Hagiwara et al 2007). In the auditory system, total body heat stress is protective against noise-induced hearing loss (Yoshida et al 1999).…”
Section: Figmentioning
confidence: 99%
“…Heat shock proteins have been proven to play a key role in protecting stressed cell and organisms, and preventing or reversing disorders caused by stress (Barbe et al, 1988). The protein acts as a molecular chaperone by binding to other cellular proteins, assisting intracellular transport, and folding into the proper secondary structures and thus, preventing aggregation of protein during stress (Chirico et al, 1988).…”
Section: Introductionmentioning
confidence: 99%